Beholder - La Sala, Ryan (Push, an imprint of Scholastic, Inc., 2023)
"From Ryan La Sala, author of the tantalizingly twisted The Honeys and riotously imaginative Reverie, comes a chilling new contemporary fable about art, aesthetic obsession, and the gaze that peers back at us from behind our reflections. No one survived the party at the penthouse. Except Athan. Athanasios "Athan" Bakirtzis has made it far in life relying on his charm and good looks, even securing an invitation to a mysterious penthouse soiree for New York City's artsy elite. But when he sneaks off to the bathroom, he hears a slam, followed by a scream. Athan peers outside, only to be pushed back in by a boy his age. The boy gravely tells him not to open the door, then closes Athan in. Outside the door, the party descends into chaos. Through hours of howls, laughter, and sobs, Athan stays hidden. When he finally emerges, he discovers a massacre where the corpses appear to have arranged themselves into a disturbingly elegant sculpture--and Athan's mysterious savior is nowhere to be found. Athan--the only known survivor--is now the primary suspect. In a race to prove his innocence, Athan is swept up in a supernatural mystery, one of secret occult societies and deadly eldritch horrors with rather distinctive taste. Something evil is waking up in the walls of New York City, and it's compelling victims toward violence, chaos, and self-destruction. Bound to him by a mysterious hereditary power, Athan has felt this evil hiding behind his reflection his entire life, watching him. Waiting. Now, it's taking over"--